PEMBENTUKAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes) DALAM PRESPEKTIF GOOD GOVERNANCE - Indah Maulidiyah (Legalita, 2020)
The scope of structuring an absolute democratic system is an effort to involve various elements such as from the government administration, residents and business owners who are tasked with creating an absolute government. The sector that plays the main role in creating a constitutional order that makes the basic foundation for carrying out services provided by regional leaders and ranks in accordance with state authorities (Encik Muhammad Fauzan, 2017: 251). The village is an area where there are people who inhabit and live and whose rights are protected by law, there are certain coordinate points as a sign of boundaries between areas of legal community units. The duties and responsibilities of the village government authorities are to run the government on a foundation for and by the people. This is stated in the regulation in article 1 point 1 of Law Number 6 of 2014 concerning Villages. Meanwhile, the village (hamlet) is defined as the administrator of the state which involves the affairs of the people as the driving force for the wheels of government (Sirajudin and Winardi, 2016: 336)